Rolling stock: library and information services for gypsies and travellers - Webb, K (K. G. Saur Verlag, 2005)
Gypsies and Travellers have lived in Britain for over 500 years and yet the country’s ‘original and oldest ethnic minority’ (Pateman 2004, 42) remains the least tolerated by the majority. This paper provides a brief cultural analysis based on the Gypsy Traveller way of life and how current policies and service provision create barriers to this culture and tradition. Library and information service requirements are identified in relation to specific needs, based on the issues that directly affect this minority group. An examination of current policies and service provision will also identify existing barriers to enabling access to information. Proposals are made for providing library and information services appropriate to this minority community, in order to break down these barriers, enable access to information pertinent to their needs and tackle the issues that contribute to the social exclusion of the Gypsy Traveller community in Britain.